The efficiency of the human sense and its impact in assessing the historical sustainability of the city, urban and architectural - Arbil city in Iraq model -: كفاءة الاحساس الانساني وأثره في تقييم استدامة المدينة التاريخية عمرانيا ومعماريا - مدينة اربيل في العراق أنموذجا - - Nesma Maan Mohamed Thabet - Rasha Abdel Karim Ali El Nagdy, (Journal of engineering sciences and information technology, 2017)
Design as fine art concerned with the beautiful and appeal to the eye, just as music appeals to the ear, and the external appearance of urban design and architectural product is only one of several factors which interest architect and urban designer when they judge a building or a city, architecture and urban design as something indivisible, something you can't separate into a number of elements. They aren't produced simply by adding sites, plans , sections and elevations , they are limit by no means well-defined. This study will discusses and explains precisely what architecture and urban design are ,they must be experienced as fine arts. The architect and urban designer work with form and mass just as the sculptor does, and like the painter he works with color, but alone of the three ,his is functional art. The current research tackles the study of urban design and architectural experienced the efficiency of human sense and it's effect on sustainability of historical cities within the designing process. The research discusses the importance of this concept in order to explore the particular problem represented by the unclarity of the concept role in urban design and architectural products, Therefore the problem of the paper was crystallized and its objective and methodology were identified by studying urban design and architectural product experienced as color shapes and it's relation with designer and designing process, reading the determination the theoretical framework, that involved two main items of detailed theoretical field , Which limit the concept in urban design and architecture ,firstly, Then applying operations are submitted which represented by electing the measurement vocabularies and electing the projects in the historical cities and crystallized the hypothesis, secondly, at last  discussing  the results to submit the conclusions in the end, which showed that the difference in the nature of practicing the concept (Efficiency of human sense and its effect on sustainability of historical cities) depend on many factors like designer's trends and another factors especially in Erbil city in Iraq .